Long‐term outcomes in healthy adults after radiofrequency ablation of T1a renal tumours. (8th November 2013) - Ma, Yunbo; Bedir, Selahattin; Cadeddu, Jeffrey A.; Gahan, Jeffrey C.
<x xml:space="preserve">Abstract</x> Objective To report the long‐term oncological and renal function outcomes in healthy adults treated with radiofrequency ablation (RFA) for small renal masses. Materials and Methods We retrospectively analysed the medical records of otherwise healthy patients (those with American Society of Anesthesiologists symptom score 1 or 2) with clinical T1a renal tumours who underwent RFA at our institution between March 2001 and July 2012. Radiographic follow‐up with contrast imaging was performed at 6 weeks, 6 months, 1 year and annually thereafter. Local recurrence was defined as any new enhancing lesion (>10 HU) after the initial negative post‐treatment computed tomography results. The estimated glomerular filtration rates (eGFRs) before and after RFA were calculated using the Cockgroft–Gault equation. Results We performed RFA on 58 renal tumours in 52 patients. The mean tumour size was 2.2 cm with a median (interquartile range) follow‐up of 60 (48–90) months. Three (5.1%) of the treated masses had tumour recurrence after initial RFA. The 5‐ and 10‐year recurrence‐free survival rate was 94.2%. There were no recurrences after 3 years. Three (5.1%) patients died during the follow‐up, which gave 5‐ and 10‐year overall survival rates of 95.7% and 91.1%. No patient developed metastatic renal cell carcinoma (RCC) and none died from RCC. Paired analysis showed that the eGFR values at a median follow‐up of 40 months did not differ significantly from those before RFA. Conclusion With long‐term follow‐up, RFA provides durable oncological and functional outcomes for selected T1a renal tumours in otherwise healthy patients.